Facing the challenges of whole-school reform : New American Schools after a decade - Berends, Mark, 1962-; Bodilly, Susan J.; Kirby, Sheila Nataraj, 1946- (Rand Education, 2002)
After a decade of studies, this report released in 2002, draws together RAND's research on New American Schools, highlighting the organizations significant contribution to comprehensive school reform and noting the challenges that came with implementing whole-school designs.